Um útero todo seu: público e privado nos posts sobre aborto das Blogueiras Feministas - Michele Cristina de Assis Dutra (2013)
This dissertation examines how the relationship between the public and private spheres manifests itself in posts regarding abortion in the Blogueiras Feministas blog. The public/private divide is fundamentally relevant in feminist theory, simultaneously representing descriptive and normative dimensions. Abortion, and more specifically the demand for its legalization, is subject dear to feminism and the discussion it elicits often crosses the public and private spheres. By addressing abortion, the bloggers examine issues intimately associated with this divide, such as the roles of the individual, the State and the Church, and the rights of women and embryos/fetuses. Based on this movement, the configurations of these spheres are constantly reimagined, as are the current or desired boundaries that separate them. During specific moments, these boundaries take on a more fluid character, whereas in others, there is a clear delimitation of what is public and what is private.